The Extent In Which High School Teachers Of History Practice Classroom Procedural That Develop Historical Thinking Of Their Students In The City Of Zakho - Haji, Sattar J. (Humanities Journal of University of Zakho, 2017)
This research aims to reveal the extent in which teachers of History practice classroom procedures to develop historical thinking of High school students in Zakho city. To investigate this, the researcher prepared a tool that contained (20) classroom procedures that develop historical thinking. The tool was successfully piloted for its validity and reliability. Then, it was applied on 30 teachers (15) male and (15) female from the directory of education in the city of Zakho. The date was collected through direct classroom observation. The results showed that the teachers of History practice most of the classroom procedures which develop historical thinking skills of their students. However, other classroom procedures were not practiced up to a satisfactory level. In addition, the findings demonstrated no significant difference in gender and teachers’ years of experience. On the other hand, there was a significant difference between teachers who participated in teacher training courses and those who did not i.e. the teachers who had training performed better in applying procedures leading to developing students’ historical thinking. In the light of these findings, the researcher recommends the following. Firstly, classroom procedures that develop historical thinking should be included in teachers’ university syllabus. Secondly, the directory of Education in Zakho should resume pre-service teacher training courses for its teachers and include those procedures in the programme